Scienceploration Camp 2016 - Dhana Jay, A/L Raja Gopal; Tan, George Geok Shim; Rohaiza, Binti Daud (Centre for Pre-University Studies, 2016)
The Scienceploration Camp is an initiative of the Centre for Pre-University Studies, UNIMAS, aimed to increase the interest in science among secondary school students and SPM leavers. The camp has two main objectives; to provide various fun scientific activities and to increase the visibility of the Centre for Pre-University Studies as one of the best option for post secondary education.